The effect of thermal annealing on linear and nonlinear optical response of dyed KDP crystals - Pritula, I.; Gayvoronsky, V.; Gromov, Yu.; Kopylovsky, M.; Kolybaeva, M.; Puzikov, V.; Kosinova, A. (Functional Materials, 2008)
Potassium Dihydrogen Phosphate crystals (KDP) doped with the organic Xylenol Orange (XO) dye are grown, the XO concentration in the crystal matrix is about 10 ppm. The spectral and luminescent properties of nominally pure, dye-doped and the dyedoped/annealed at 150°C crystals (KDP, KDP:XO and KDP:XOan) are measured. The annealing temperature effect on the degree of dye protonation in the crystal matrix is established. Analysis of the IR-absorption spectra reveals a strong interaction between the incorporated dye molecules and the hydrogen subsystem of the matrix. The nonlinear optical (NLO) properties of KDP, KDP:XO and KDP:XOan crystals are studied within the self-action effect of picosecond laser pulses at 532 nm. The mechanism of photoinduced bleaching and the effects of laser beam self-focusing (in KDP) and self-defocusing (in KDP:XO and KDP:XOan) are supposed to be due to resonance excitation of the subsystems of intrinsic defects and dye molecules, correspondingly. For KDP:XOan it is shown thermal annealing of intrinsic crystal defects leads to domination of more effective NLO response of the subsystem of dye molecules that is correlated with photoluminescence data.